The Concept of Wakālah and Modern Agency in Contemporary Islamic Law - Sigit Prian; Suhartono; Rifqi (Penerbit Hellow Pustaka, 2025)
This research aims to analyze the concepts of wakalah and agency from a contemporary Fiqh perspective, focusing on their relevance in modern transactions. The research design employs a comprehensive library research method, examining various primary and secondary literature related to Fiqh muamalah, Islamic contract law, and agency practices in the contemporary era. The main findings indicate that although the concept of wakalah has strong roots in classical Fiqh, its application in the form of modern agency requires careful interpretation and adaptation to suit current economic dynamics. A fundamental distinction between wakalah as pure representation and agency as a commercial activity needs to be understood to avoid legal ambiguity. The implication of this research is the importance of developing a more adaptive Fiqh framework to accommodate complex agency practices, ensuring sharia compliance while remaining relevant to market needs. This implication encourages Islamic financial institutions and legal practitioners to draft more transparent and sharia-compliant contracts for agency transactions. The originality of this research lies in its comparative analysis between traditional wakalah and modern agency concepts from a contemporary Fiqh perspective, providing a theoretical foundation for the development of innovative sharia-compliant products and services within the realm of agency.